Employer perspectives on the living wage and minimum wage during Covid: evidence from New Zealand. (2nd January 2023) - Arrowsmith, James; Parker, Jane
ABSTRACT: New Zealand is a relatively low wage economy but living costs are high and rising. One government response has been to accelerate the Minimum Wage (MW) which is now converging on the Living Wage (LW) rate. This paper explores employer attitudes and practices regarding the LW, in the context of the rising MW and Covid disruption, based on a survey of over 600 organisations. Motivation for adopting the LW simultaneously derived from ethical considerations of fairness, especially given higher living costs, and prospective returns such as better recruitment, retention and motivation in the context of tighter labour markets. Implementing the LW had mixed employment effects with benefits more likely to accrue to larger organisations. However, difficulties relating to wage differentials were also more acute in larger firms. Where affordability inhibited the full restoration of wage differentials, which were narrowing in many organisations due to the higher MW or adoption of the LW, this resulted in a perceived inequity for relatively higher paid employees. The findings highlight how perceptions of 'fairness' may vary. This could limit the wider adoption or potential gains arising from the LW, and employment relation processes need to be configured to defuse such potential indirect effects.